Evaluating oregano oil as a growth enhancer in nursery pig diets - Neill, C.R.; Groesbeck, C.N.; Lawrence, K.R.; Hastad, C.W.; Gottlob, R.O.; Hildabrand, B.M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 224 nursery pigs (PIC L 327L × C22) initially 12.9 ± 3.0 lb and 21 d of age were used in a 28-d feeding trial. The objective of our study was to evaluate the effects of oregano oil, with or without an in-feed antimicrobial. Oregano oil is a plant extract derived from the Greek herb, Origanum vulgare. It has been speculated to have antimicrobial-like activity. There were four dietary treatments in a 2 × 2 factorial. Diets consisted of a negative control (without an antibiotic or oregano oil), the control diet plus neomycin/oxytetracycline (140 g/ton), the control diet plus oregano oil, or the control diet with both neomycin/ oxytetracycline and oregano oil. The oregano oil (5%) was added to an inert carrier (95%) to make a premix that was added to the diet at 2 lb/ton in phase 1 (d 0 to 14) and 1 lb/ton in phase 2 (d 14 to 28). During the 28-d trial, neomycin/oxytetracycline improved ADG, ADFI and F/G. Pigs fed dietary treatments containing neomycin/oxytetracycline had the heaviest average weights at the end of the trial. Adding oregano oil to nursery pig diets did not improve ADG, ADFI, or F/G during the 28-d trial.
Keywords: Nursery pigs; Neomycin/Oxytetracycline; Swine; Oregano; Pigs